Geriatric Patients on Antithrombotic Agents who Fall: Does Trauma Team Activation Improve Outcomes?. Issue 7 (July 2019) - Hwang, Peter; Ong, Adrian W.; Muller, Alison; Mcnicholas, Amanda; Martin, Anthony; Sigal, Adam; Fernandez, Forrest B.
Despite the incorporation of anticoagulant and antiplatelet (ACAP) drugs in our trauma triage criteria, it is unclear whether trauma team activation (TTA) impacts outcomes in geriatric patients on ACAP drugs sustaining falls. We hypothesized that TTA in this cohort was associated with improved outcomes. The hospital electronic database was queried to identify normotensive, awake patients aged ≥65 years on ACAP agent from 2014 to 2018 presenting to the emergency department after falls. The outcome was in-hospital mortality. The association between TTA and mortality was examined using logistic regression analysis and 1:1 propensity score matching analysis. In this study, 4540 patients on ACAP drugs were analyzed, with TTA occurring in 500 (11%). TTA occurred in younger but more severely injured patients with lower Glasgow Coma Score. Logistic regression revealed that TTA was not associated with mortality (odds ratio [95% confidence intervals], 2.04 [0.89–4.25]). The 1:1 propensity score analysis revealed similar mortality for the matched groups (non-TTA, 1.6% vs TTA, 2.2%, P = 0.64). In the elderly patients on ACAP agents, the current triage criteria resulted in the appropriate use of TTA for more severely injured patients. The lack of outcome benefit suggests that ACAP drug use as a criterion for TTA should be re-evaluated.